STUDI KOMPUTASI INTERAKSI ZEOLIT LTA (LINDE TYPE A) DENGAN KATION ALKALI (LI+, NA+, K+) MENGGUNAKAN METODE MEKANIKA MOLEKULER - Audi Zahid Iswaradi; Rahmat Gunawan; Noor Hindryawati (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2021)
A study of computation on zeolite LTA (Linde Type A) interaction with alkaline cation (Li+, Na+, K+) using the mechanical molecular method was conducted. Data processing was conducted computationally using Hyperchem 7.0 with the mechanical molecular method. The result of the study showed zeolite LTA with ratio Si/Al 2,4286 has the lowest minimum energy. Furthermore, impregnation by cation Li+ increases structure stability, and impregnation by cation Na+ has the largest diameter window on Zeolite LTA.